Avaliação da eficácia, disponibilidade, características e usabilidade de aplicativos móveis de saúde para pessoas com Diabetes - Bráulio Cezar Bonoto (2016)
Diabetes Mellitus (DM) is a chronic disease, considered a global public health problem. Education and self-monitoring of diabetes patients aims to improve health outcomes, as example, glycemic control. The global growth of smartphones users make them a powerful platform to help provide health care individually through health applications (apps). These have several features to aid in control or treatment of diseases and improve health style. The technology efficacy assessment was done a systematic review and meta-analyses from randomized clinical trials. To assess apps found characteristics and usability was realized search in three main app stores Google Play, iTunes and Windows Phone. Apps presented favorable results to glycated hemoglobin control if patients have remote access to health professionals. Despite favorable results, most of available apps are not ready to achieve satisfactory patients results and not have a good quality of usability.